Morbidity and mortality profile of neonates admitted in special newborn care unit of a teaching hospital in Uttarakhand, India - Kumar, Rakesh; Mundhra, Rajlaxmi; Jain, Anand; Jain, Suchitra (International Journal of Research in Medical Sciences, 2018)
Background: India accounts for 24% of global neonatal mortality. It is important to study the mortality and morbidity pattern as it helps to implement new treatment protocols, interventions, planning and policy making which helps in better survival and improvement in the quality of life among survivors. The aim of the project study was to determine the causes of morbidity and mortality in neonates admitted in our hospital. Methods: This study was conducted at Special Newborn Care Unit (SNCU) of Veer Chandra Singh Garhwali Government Institute of Medical Science and Research providing level II neonatal care. This is a retrospective hospital based observational study. Data from admission and discharge registers were extracted, compiled and analyzed from March 2016 to February 2018. Neonates taken against medical advice and those referred to tertiary care centers were excluded in calculation of survival outcome. Statistical analysis was done in form of percentage, proportions and chi square test was used to find statistical significance. Results: 1582 neonates were admitted during the study period. 60.80% were inborn and 39.20% were outborn. 59.54% were male and 40.46% were female. Major causes of admission were jaundice (24.72%), sepsis (20.48%), birth asphyxia (18.52%), meconium aspiration syndrome (10.11%). Birth asphyxia was the major cause of mortality, followed by sepsis and prematurity. Mortality was more in outborn babies 14.67% compared to inborn babies 9.80%. Conclusions: Neonatal jaundice, birth asphyxia and sepsis were the commonest causes of morbidity. Common causes of mortality were birth asphyxia and sepsis and prematurity. More deliveries at institutions with SNCU facility, early identification of danger signs and timely referral to tertiary care centers can prevent neonatal deaths.